THE USE OF ACADEMIC VOCABULARY ACROSS PROFICIENCY LEVELS: A STUDY OF EFL STUDENTS’ LEXICAL PERFORMANCE IN UNIVERSITY WRITING - Christianus I Wayan Eka Budiartha (ELTR Journal, 2020)
This study aims to investigate EFL students’ performance in recognizing and using academic vocabulary across three different proficiency levels of English, i.e., elementary, intermediate and advanced. A quantitative approach was employed with a cross-sectional design to examine the difference and the correlation between the two variables and 150 subjects from a private university in Jakarta, some interesting results were uncovered in this study. First, there was a significant difference in overall calculation of students’ academic vocabulary across proficiency levels, even though such a difference does not appear between intermediate and advanced level. Second, the overall calculation shows that there was a significant correlation between students’ academic vocabulary and their proficiency levels with Sig. 0.249, but surprisingly, a more detail calculation did not present any correlation at all between the variables. These results confirm that the gap among proficiency levels was not big, as majority of the students were in intermediate level of their English competence. Even though the students could perform academic vocabulary in university writing; however, almost all of them were not aware with the existence of the words, especially because the words belong to the low frequency band.